Weather watcher - Woodward, John. (London : Dorling Kindersley, 2006)
Presents photo-illustrated step-by-step instructions for more than thirty weather study activities, covering such topics as solar energy, air pressure, fronts, wind speed, morning dew, and ice.
Keywords: Meteorology -- Juvenile literature; Weather forecasting -- Juvenile literature; Weather -- Experiments -- Juvenile literature